Seroprevalence against SARS-CoV-2 after booster vaccination in a prison in Alicante (Spain) - Montagud, Ana C.; Moragues, Raul; Vicente-Alcalde, Nancy; Montagud, Emilia; Hurtado-Sánchez, José Antonio; Tuells, José (Frontiers in Public Health, 2025)
BackgroundConfinement conditions in prison communities are associated with increased susceptibility to infectious outbreaks. The COVID-19 pandemic has been characterized by high transmissibility and clinical severity resulting in a high number of infections and deaths worldwide. Vaccination has been a crucial tool in mitigating its devastating effects. The aim of this study is to asses the prevalence of antibodies against the Spike protein of SARS-CoV-2 in vaccinated prisoners and staff at a specific prison in Alicante.MethodsA cross-sectional epidemiological study was designed for the population in scope using a rapid lateral flow immunochromatography serological test, conducted on July 27, 2023. Demographic and clinical variables were collected through a questionnaire. Statistical analysis was performed using the SPSS 29.0 software.ResultsA total of 560 people participated in the study; the predominant profile was men (77.3%) with an average age of 45.7 years. 71.4% of subjects were prisoners and 28.6% were prison staff. Regarding the detection of anti-SARS-CoV-2 antibodies obtained through serological test, 60.9% of the sample gave a positive result. 69.1% of participants received the last dose in 2022 or later and 62.2% received booster doses. The vaccines administered in the last dose were Biontech/Pfizer and Moderna in 88.6% of the cases. 59.5% of sample had suffered from COVID-19 and 67.0% did not have any clinical comorbidity. In the regression analysis, it was observed that the variables with a stronger statistical relationship with presence of anti-SARS-CoV-2 antibodies were: the number of years since last vaccine dose was received (aOR: 0.08; 95%CI: 0.05; 0.16) the number of vaccine doses received (aOR: 4.8; 95%CI: 2.9; 8.0) and presenting any comorbidity (aOR: 4.3; 95%CI: 2.4; 8.0). The staff received more booster doses and obtained a better response to seropositivity, with 72.5% of anti-SARS-CoV-2 result positive while prisoners reached 56.3%.ConclusionThe COVID-19 vaccination status within the prison community following the initiation of primary immunization and subsequent booster doses, shows a low immunization coverage (60.9%), which is below expectations given the immunization strategies implemented since the start of the pandemic. There are notable differences in vaccination rates between prison staff and prisoners. These disparities are concerning, and authorities responsible for prison public health should take a more proactive approach to ensuring vaccination among prisoners.